2019
DOI: 10.1021/acsabm.9b00483
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles Doped with Gold Nanoparticles for Combined Cancer Immunotherapy and Photothermal Therapy

Abstract: Cancer immunotherapy is a treatment that utilizes the host immune system to fight against cancer. Inducing a cancer antigenspecific adaptive immune response is key in cancer immunotherapy. Although diverse immune cells including dendritic cells (DCs) and T cells infiltrate a tumor, the activation of such immune cells is inhibited, owing to an immunosuppressive tumor microenvironment. In this study, we propose mesoporous silica nanoparticles (XL-MSNs) decorated with gold nanoparticles (Au@XL-MSNs) for the deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 56 publications
(82 reference statements)
0
24
0
2
Order By: Relevance
“…Moreover, these NPs decreased the intracellular glutathione (GSH) level and increased the ROS (reactive oxygen species) level which further induced strong cytotoxic T cell (CD8 + T cell) response as well as enhanced antitumor activity. In another study, Ong et al ( 2019 ) decorated extra-large porous MSNs with small GNPs for effective delivery of CpG-ODNs into DCs. They showed that delivery of CpG-ODNs using such nanoplatform enhanced the expression of co-stimulatory molecules as well as increased the secretion of pro-inflammatory cytokines (IL-12 and TNF-α) as compared to soluble CpG-ODNs in vitro .…”
Section: Types Of Nanoparticles For Immunostimulationmentioning
confidence: 99%
“…Moreover, these NPs decreased the intracellular glutathione (GSH) level and increased the ROS (reactive oxygen species) level which further induced strong cytotoxic T cell (CD8 + T cell) response as well as enhanced antitumor activity. In another study, Ong et al ( 2019 ) decorated extra-large porous MSNs with small GNPs for effective delivery of CpG-ODNs into DCs. They showed that delivery of CpG-ODNs using such nanoplatform enhanced the expression of co-stimulatory molecules as well as increased the secretion of pro-inflammatory cytokines (IL-12 and TNF-α) as compared to soluble CpG-ODNs in vitro .…”
Section: Types Of Nanoparticles For Immunostimulationmentioning
confidence: 99%
“…We also compare the cell viability data with the other gold nanoparticle hybrid and showed that 1-AuNPs remained nontoxic to the A549 cells in the dark, but in the presence of red light, it exhibited optimal toxicity (Table S7). [81][82][83][84][85][86][87][88] The IC 50 value of complex 1 was determined to be 89.0 and 39.2 μM in dark and red light, respectively ( Figure S36).…”
Section: Photocytotoxicity Assaymentioning
confidence: 99%
“…Apart from the combination of immunostimulants, Kim and co‐workers also explored the potential of combined immunotherapy plus PTT. [ 76 ] To do so, the authors have employed large pore MSNs to load small AuNPs (1−2 nm) suitable for PTE. Finally, to complete the system, the loaded AuNPs were functionalized with thiol‐modified CpG and PEG moieties to add the desired immunostimulant feature and to provide enough colloidal stability.…”
Section: Combination Therapies Based On Immune Stimulationmentioning
confidence: 99%